Mrs. jeffries delivers the goods eaudiobook - Brightwell, Emily (Mrs. Jeffries, 2020)
When poison fells an arrogant and rude businessman in public, Mrs. Jeffries and Inspector Witherspoon both realize they are looking for a deranged maniac in this new installment of Emily Brightwell's beloved mystery series. On a cold night in February, the popular Lighterman's ball festivities are cut short when a guest of honor, Stephen Bremmer, goes into spasms and abruptly collapses. Once again Inspector Witherspoon returns to the Wrexley Hotel to investigate a murder. The victim was considered a boorish snob who felt entitled to anything and anyone he wanted. Yet despite his Oxford education, he was barely literate, lazy, and prone to make stupid mistakes—his last mistake turned out to be crossing a killer. The owners and management of the Wrexley Hotel clearly don't welcome the return of Inspector Witherspoon but he has his job to do, and Mrs. Jeffries, and the rest of the household must do their best to catch a murderer who shows no signs of slowing down . . .